Understanding consumer impulse buying in livestreaming commerce: The product involvement perspective - Gong, Xiaoxiao; Jiang, Xuetao (Frontiers in Psychology, 2023)
The rapid development of livestreaming commerce has received widespread attention from both theoretical and practical circles. However, relatively few studies have been conducted from a product perspective, and even fewer studies have analyzed product characteristics influencing consumers’ impulse buying based on product-involvement theory. Grounded on product involvement theory, this study proposed a theoretical research model and empirically tested the model using online survey data collected from 504 livestreaming consumers in China. The results showed that functional for money, perceived product quality, perceived product scarcity, instant feedback on product information, and perceived product knowledge of streamers can drive product cognitive and affective involvement, which, in turn, induce the consumer-felt urge to buy impulsively and engage in impulse buying behavior. However, the functionality of product design can only affect the product cognitive involvement, not the affective involvement. Implications for research and practice are discussed.